Spreading Effect of Enhanced Blast in Explosives and Propellants - Partom, Yehuda (European Journal of Applied Sciences, 2023)
We performed tests on one of our propellants to determine its TNT equivalence. In such tests we detonate a charge of explosive at one end of a propellant cylindrical sample. We use two types of diagnostics: 1) to determine the propellant energy release rate, we wrap it with a thin aluminum shell, and measure the radial velocity of the shell along the propellant sample with velocity interferometers (PDV); and 2) we use commercial blast gauges at a distance of about 10m from the test sample, to determine the blast effect of the propellant (after deducting the blast effect of the driving explosive). We expected the two types of diagnostics to agree with one another, but this has not been the case. From the velocity gauges we see that only the part of the propellant which is near the explosive has fully reacted, and that the extent of this part depends on the size and configuration of the driving explosive. But from the blast diagnostics it seems, that as if the whole propellant has reacted. We’ve seen some sporadic indications in the literature to such an enhanced blast effect from propellants [1-5]. We refer here to such an enhanced blast effect as a spreading effect. We claim, that when a reacting propellant (or explosive) is spread out in space (without changing its total energy release upon reacting), the blast effect at a given distance is enhanced substantially compared to the same energy yield without spreading. In our tests, the relative amount of reacted propellant decreases substantially with distance from the initiating explosive, but because it does not react in a continuous fashion, there is a spreading effect, that enhances the level of air blast substantially. To demonstrate the action of the spreading effect, we make 1D simulations of outgoing detonations of an HB (H=HMX, B=Binder) explosive in spherical symmetry. For different runs we dilute the explosive with the binder to various extents, from W=1 (pure explosive) to W=0.01 (1% explosive). For each such formulation we compute the detonation parameters using our in-house chemical equilibrium code (not presented here). For each formulation we adjust the explosive radius so that the total detonation energy stays the same. For all runs we monitor the rigid boundary reflected pressure (pr) of the created blast wave in air, at a radial distance of 12m. We get that as W decreases below 0.5, the total amount of HMX decreases below 6% of the amount for pure HMX, but pr increases by about 12% relative to that of pure HMX. We attribute this enhanced blast effect to the spreading of the explosive, while keeping the amount of energy released unchanged (spreading effect).